2015
DOI: 10.1002/art.39211
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 Variant R620W Is Associated With Reduced Toll‐like Receptor 7–Induced Type I Interferon in Systemic Lupus Erythematosus

Abstract: Objective Protein tyrosine phosphatase nonreceptor type 22 (PTPN22) is associated with an increased risk of systemic lupus erythematosus (SLE). PTPN22 encodes Lyp, and a disease‐associated coding variant bears an R620W substitution (LypW). LypW carriage is associated with impaired production of type I interferon (IFN) by myeloid cells following Toll‐like receptor (TLR) engagement. The aim of this study was to investigate the effects of LypW carriage on TLR signaling in patients with SLE. Methods Plasma IFNα co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 57 publications
(105 reference statements)
1
37
0
Order By: Relevance
“…Although SLE is generally associated with a type I IFN signature, it has been recently shown that pDC production of type I IFN is impaired in patients carrying a variant of the PTPN22 gene predisposing to SLE 211 . This observation raises the question of whether pDC and type I IFN depletion is a valid strategy for all SLE patients or should be adopted after stratification of the patients for pDC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although SLE is generally associated with a type I IFN signature, it has been recently shown that pDC production of type I IFN is impaired in patients carrying a variant of the PTPN22 gene predisposing to SLE 211 . This observation raises the question of whether pDC and type I IFN depletion is a valid strategy for all SLE patients or should be adopted after stratification of the patients for pDC activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in this clear-cut picture many questions remain open. For example, pDC production of type I IFN is impaired in SLE patients carrying a variant of the PTPN22 gene [256], raising the possibility of a different pathogenic mechanism as well as the hypothesis that pDC targeting should be adopted after patient stratification for pDC activity. It also remains to be established the possible role of these cells in other inflammatory diseases, such as inflammatory bowel diseases.…”
Section: Discussionmentioning
confidence: 99%
“… showed that Lyp promotes TLR‐induced type I IFN through interactions with TRAF3 resulting in increased TRAF3 K63‐ubiquitinylation and that Lyp620W does not have this function. More recently, this group followed up their findings in primary human plasmacytoid DC from patients with SLE comparing those homozygous for the PTPN22 ‐1858C allele to those carrying one or two copies of the PTPN22 ‐1858T allele . In this study, the authors found that pDCs carrying the PTPN22 ‐1858T allele produced less TLR7‐induced IFNα than PTPN22 ‐1858C/C homozygotes.…”
Section: Tlr Regulation By Lyp and The Autoimmunity‐associated Lyp620mentioning
confidence: 89%